An estimation for the generalized ternary ring homomorphism on non-Archimedean ternary Banach algebras - Ismail Nikoufar (Miskolc Mathematical Notes)
In this paper, we introduce the notion of the generalized ternary ring homomorphism on non-Archimedean ternary Banach algebras. Using fixed point methods, we prove the superstability and generalized Hyers-Ulam stability of generalized ternary ring homomorphisms on non-Archimedean ternary Banach algebras associated with a Cauchy-Jensen type functional equation.